Breastfeeding during the COVID-19 pandemic: Integrative review (Research, Society and Development, 2021)
The aim of this study is to understand how the COVID-19 pandemic influenced the breastfeeding of pregnant women during this period. It refers to an integrative review study, conducted in January 2021. Thus, the outline of this study arose from the following research question: what is known so far in the scientific literature on breastfeeding during the COVID pandemic -19? After going through the methodological steps, it was possible to identify 08 articles and all publications are dated in the year 2020 and focused on breastfeeding in times of pandemic. According to what was discussed in the present article, the objective was duly contemplated, demonstrating through the studies used as the basis for this review about breastfeeding through the pandemic scenario of COVID-19. In view of this, it becomes feasible to continue studies on the topic and to make future publications with new updates on the subject. Due to the fact that it is a disease that there is still much to discover, new productions in this scenario are essential.